2012
DOI: 10.1177/0091270010388648
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Dosing Versus Body Size—Based Dosing of Therapeutic Peptides and Proteins in Adults

Abstract: Therapeutic biologics are often administered based on body size. A previous study has found that fixed dosing performs similarly to body size-based dosing in reducing intersubject variability in drug exposure across the mAbs studied. This study extended this evaluation to other therapeutic proteins and peptides. Eighteen therapeutic proteins and peptides with published population pharmacokinetic (PK) and/or pharmacodynamic (PD) models were selected for dosing approach evaluation. The relationships between body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Two retrospective studies evaluated the potential benefits of fixed dosing and body size-based dosing by comparing the ability of each of the two approaches to reduce pharmacokinetic (PK) and/or pharmacodynamic (PD) variability in adults for 30 biologics with published population PK and/or PD models [24,25] . Of these 30 biologics, 1 2 were mAbs [24] , and 18 were not mAbs (these included therapeutic proteins and peptides) [25] .…”
Section: Model-based Drug Development For Biologicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two retrospective studies evaluated the potential benefits of fixed dosing and body size-based dosing by comparing the ability of each of the two approaches to reduce pharmacokinetic (PK) and/or pharmacodynamic (PD) variability in adults for 30 biologics with published population PK and/or PD models [24,25] . Of these 30 biologics, 1 2 were mAbs [24] , and 18 were not mAbs (these included therapeutic proteins and peptides) [25] .…”
Section: Model-based Drug Development For Biologicsmentioning
confidence: 99%
“…Of these 30 biologics, 1 2 were mAbs [24] , and 18 were not mAbs (these included therapeutic proteins and peptides) [25] . At the population level, the inter-subject variability in exposure (AUC and C max ) was examined for 1000 subjects, for both dosing approaches.…”
Section: Model-based Drug Development For Biologicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of body weight on PK parameters has been well described by Wang et al 36 as well as Zhang et al 37 In their initial review Wang et al found that fixed dosing performed similarly to body weight-based dosing in reducing intersubject variability in drug exposure across the therapeutic proteins studied. Zhang et al expanded the evaluation to other therapeutic proteins and peptides and included 18 therapeutic proteins and peptides with published population PK and/or PD models to evaluate the 2 dosing approaches: flat fixed vs body weight-based dose (see Figure 2).…”
Section: Body Weight-based Dosingmentioning
confidence: 92%
“…They also recommended that the final dosing approach for phase 3 studies should be determined based on a full assessment of body size effect on PK-PD when sufficient data become available and the therapeutic window of the drug is better understood. 37 Discussion After a review of current therapeutic protein approvals, including the latest nivolumab approval of flat fixed dose, 38 most biologics including the therapeutic proteins utilize a flat fixed-dose approach. The nivolumab approval to move from body weight-based dosing to flat fixed dose was based on population PK analyses and dose/exposure-response analyses demonstrating comparability of the PK exposure, safety, and efficacy of the proposed new dosing regimen to the previously approved body weight-based regimen.…”
Section: Body Weight-based Dosingmentioning
confidence: 99%